Effects of a Deeper Central European Free Trade Agreement - Mulabdic, Alen (Washington, DC: World Bank, 2022)
This paper studies the economic effects of ‘deepening’ the Central European Free Trade Agreement (CEFTA). It combines new information on the content of trade agreements with gravity model estimates of the impact of deep trade agreements, agreements that go beyond the elimination of tariffs and other border restrictions. The analysis suggests that CEFTA is a relatively shallow trade agreement as it covers mostly policy areas under the current WTO mandate. The estimated trade impacts of CEFTA on member countries are relatively modest, varying between 0.02 and 7.4 percent. CEFTA’s members would gain from simultaneously deepening their integration reciprocally and vis-a-vis the EU. In particular, a trade agreement with the EU similar to the EU-Norway agreement could increase total exports by CEFTA members between 4 and 27 percent.